Coconut Shell Turtle Crafting Souvenir Training for Pokmaswas Women in Masaran Village, Trenggalek - Garsione Agni Andrea; Muhammad Dedy Yanuar; Praja Firdaus Nuryananda; Wahyuni (Nusantara Science and Technology Proceedings, 2022)
Masaran Village is one of the tourist villages located in Trenggalek Regency. This village is located adjacent to the south coast with a distance of approximately 40 km from the district government center. Masaran Village has also developed various tourist attractions and activities offered to tourists, including mangrove education and turtle conservation, beach safaris, fun games, camping tours, outbound. The Mutiara Laut Sumbreng Pokmaswas was established in 2013 located in Masaran Village, Munjungan District. This community group, which is active in turtle conservation and beach cleaning, consists of 23 people, 12 of whom are women. So far, the Fisheries Service has provided more training on fish management and turtle care, so the Pokmaswas submitted assistance funds to the Village Government to conduct counseling and training, but with new regulations directing village funds to handle Covid, the Village Government has not dared to budget for training to Pokmaswas. So that the role of universities is needed in helping partner problems. The proposal team has formulated one priority issue, namely the lack of tourism innovation in the turtle conservation area in Masaran Village. Based on the priority issues above, the proposing team provided an alternative solution for the PIKAT program, namely the holding of training on making turtle souvenirs from coconut shells and coconut husks typical of Masaran Village. PIKAT community service activities are carried out using three methods, namely 1) asset-based community development (ABCD) as a method of social approach to the community, 2) counseling and training on making souvenirs from coconut shells, and 3) producing souvenirs from coconut shells in the form of turtles. turtle. Meanwhile, the mandatory outputs include print and electronic media articles, publications on YouTube, modules, intellectual property rights, and the MBKM program with a minimum conversion of 2 credits for students.